Psalmus responsorius del P.Monts.Roca inv. 128-178. Note su alcune interpretazioni controverse - Isola, Antonino (2024)
The A. compares the psalmus contra partem Donati, written by Augustin about 394, with the anonymous psalmus responsorius from a papyrus preserved in the Benedictine abbey in Montserrat, near Barcelona, under the shelf mark P.Monts.Roca inv. 128-178, dating maybe to the mid-IV century AD, from which only the strophes from A to L are complete. Particularly, he focuses on four lines before the acrostic strophes, whose reading is very controversial, and whose prosody he presents as different from the common one, restoring it fully to its function of hypopsalma: Páter qui ómnia régis péto / Chrísti nós sciás herédes / Chrístus uérbo nátus pér quem pópulús est líberátus